Effect of Phase Structure on Sintering Behavior of Zirconia Nanopowders. Issue 12 (13th November 2013) - Trunec, Martin; Castkova, Klara; Roupcova, Pavla; Franks, G.
<x xml:space="preserve">Abstract</x> Zirconia nanopowder compacts with comparable particle sizes and pore size distributions but different phase structures were prepared. The sintering behavior of monoclinic, tetragonal, and cubic zirconia nanopowders was directly compared. The densification and microstructural changes during sintering were investigated. The tetragonal and cubic nanopowders showed similar sintering behavior whereas the monoclinic nanopowder exhibited a more difficult densification and coarser microstructure compared with tetragonal and cubic powders. The differences in the densification of zirconia nanopowders resulted from significant differences in the microstructure evolution during sintering. The microstructural changes in nanopowder compacts during sintering were described and a correlation between microstructural changes and interfacial energies associated with different crystal structures was discussed.